Advocating for the Rights of Sexual Minorities within a Sectarian System - Abdel Khalek, Mazen (2020)
Despite the tolerant attitude towards same sex desire and homoerotism in pre-colonial Arab/Islamic societies, postcolonial Arab countries, unanimously condemn homosexuality. It is argued that this rejection resulted from multilayered elements such as Western colonialism and the patriarchal foundations of religious societies. With respect to Lebanon, an additional element needs to be considered: its consociational political system. In Lebanon, it is believed that the only way to ensure peace and stability is to provide political and institutional representation to the sectarian communities under a sectarian power-sharing governing framework. This sectarian system, where politics and religion are intertwined, imposes a patriarchal model of life where the only acceptable standard or norm is heterosexuality, thus legitimizing the oppression of society’s segments that do not subscribe to the patriarchal system. The blend of patriarchy and sectarianism marginalizes and discriminates against sexual minorities. This thesis shows how political sectarianism, in addition to a fragmented LGBTIQ+ community, the communitarian/minority discourse used by LGBTIQ+ NGOs and a penal code that criminalizes “unnatural-sex”, all hinder the advancement of the rights of LGBTIQ+ individuals. Given the low probability to find an alternative to the sectarian system, the LGBTIQ+ advocacy movement is obliged to navigate this system by implementing a number of strategies: moving away from identity politics, implementing an intersectional approach to include LGBTIQ+ issues in a broader social movement, and establishing alliances with political factions.